Increasing Productivity Of Oyster Mushroom Harvest By Applying Kumbung Cultivation Sanitation - Fiana, Risa Meutia; Febjislami, Shalati; Hayati, P.K Dewi (Institute of Research And Community Service, Andalas University / LPPM Universitas Andalas, 2022)
Limau Manis Village is one of the villages in Pauh District, Padang City. Oyster mushroom cultivation can be carried out by farmer groups because the technology used is appropriate technology. Oyster mushroom cultivation can use equipment that is very familiar to the community and easy to obtain. Another advantage of oyster mushroom cultivation is that land use is not too large and there are not many pest attacks on oyster mushrooms. Oyster mushroom has a very broad market. the importance of kumbung sanitation to the members of the Sejahtera Limau Manis Oyster Mushroom Cultivation Group and making improvements to the kumbung of one of the members as a pilot for an ideal kumbung design